On the link between tree size and ecosystem carbon sequestration capacity across continental forests. Issue 6 (13th June 2022) - Zhao, Meifang; Sun, Mengde; Xiong, Tao; Tian, Shihong; Liu, Shuguang
Abstract: The asymptotic height ( H max ) and the size‐scaling exponent (β), proxies of tree size and important forest architectural parameters of the relationships between height and tree diameter of forests, play important roles in the carbon (C) stocks and fluxes of forest ecosystems. However, the patterns and drivers of these values in continental China are not well known. Based on a national forest database of China, we explored the geographic patterns and ecological drivers of H max and β and their dynamic relationships with the C sequestration capabilities of the studied ecosystems, including the C stock and allocation, net ecosystem productivity (NEP), and mean ecosystem C turnover time. At the ecosystem scale, the H max values ranged from 10.37 to 37.07 m, with a mean value of 25.41 m, showing a decreasing trend with increasing latitude. However, β ranged from 0.598 to 0.73, with a mean value of 0.66, showing an increasing trend with latitude. The spatial patterns of the forest H max and β at the national scale were largely controlled by the mean annual temperature, mean annual precipitation, and forest age. These patterns were verified using biomass and forest C sequestration data, showing that the total vegetation C stock as a whole, in aboveground or belowground components, was significantly and positively correlated with H max ( p  < 0.05), revealing apparent "faster first, slower later" increasing trends with H max ( R 2  = 0.759, 0.821, and 0.527, respectively). In addition, for forest >20 m, NEP showed a significant strong negative correlation with H max (by −0.967% per 1 m of H max, R 2  = 0.504, p  < 0.05), and a 10‐m increase in H max resulted in a decrease in mean ecosystem C turnover time by 16.9% (7.43 years). Taller forests might indeed be expected to have higher autotrophic respiration consumption rates but lower mean ecosystem C turnover time and NEP values than shorter forests. The discovery that community‐level asymptotic height could be used as a comparative predictor of ecosystem C sequestration capacity and its difference among forest biomes underpins the fundamentals of ecological theories and modeling, which has important implications for forest restoration, policy, and management.